Enhancing innovation capability through relationship management and implications for performance - Panayides, Photis (My University, 2006)
Purpose - The purpose of this paper is to examine empirically the antecedents and consequences of innovativeness or innovation capability of logistics service providers (LSPs). In particular relationship orientation is examined as an antecedent to innovativeness that will in turn lead to higher levels of logistics service quality and firm performance. The outcomes aim at contributing towards understanding the main drivers of innovativeness and the outcomes of developing the capability to innovate. Design/methodology/approach - Data to empirically analyze the four research hypotheses on the relationships between relationship orientation, innovativeness, logistics service quality and firm performance are collected via a survey of a random sample of LSPs in Hong Kong and analyzed using structural equation modelling via LISREL 8.52. The LISREL diagnostics indicated good fit of the measurement and structural models, providing supporting evidence to the hypothesized causal relationships. Findings - The empirical findings indicate that relationship orientation in the LSP-client relationship will lead to higher levels of innovativeness, improvement in the quality of logistics service and improved performance for the LSP. Research limitations/implications - The study has indicated that innovativeness is influenced by relationship orientation between two partners in a business-to-business setting. The findings add credence to the relational paradigm, which suggests beneficial performance outcomes of strong relational ties. In addition, that innovativeness is an important determinant of logistics service quality and in consequence customer value and firm performance. Future research may address the issue by adopting a longitudinal rather than a cross-sectional approach and also extend the study to other industrial and cultural contexts. Practical implications - Managers should emphasize the development of client relationships and inter-organisational capabilities that can lead towards higher levels of innovativeness. The study supports the notion that the ability to provide high quality logistics services and fulfil customer requirements requires building client relationships and introducing innovations in processes and techniques. Originality/value - The originality of the paper arises from the fact that innovativeness is examined for the first time as a consequence of relationship orientation and a contributing factor to logistics service quality and performance. In this regard, the paper extends theoretical knowledge and also provides valuable managerial implications to LSPs
Keywords: Management; Business; Hong Kong (China); Logistics